Spastic paraplegia is the main manifestation of a spinocerebellar ataxia type 8 lineage in China: a case report and review of literature - Chen, Shuling; Li, Siyu; Liu, Ying; She, Renyi; Jiang, Wei (Frontiers in Human Neuroscience, 2023)
The diagnosis and treatment of cerebellar atrophy remains challenging owing to its nonspecific symptoms and laboratory indicators. Three patients with spinocerebellar ataxia type 8 caused by ATXN8OS were found among the 16 people in the studied family. The clinical manifestations of the patients included progressive spastic paraplegia of the lower extremities, mild ataxia, mild cognitive impairment, and cerebellar atrophy. After administering antispasmodic rehabilitation treatment, using oral drugs, botulinum toxin injection, baclofen pump, and other systems in our hospital, the patients' lower extremity spasticity was significantly relieved. To our knowledge, till date, this is the first domestic report of spinocerebellar ataxia type 8 affecting a family, caused by ATXN8OS with spasticity onset in early childhood. Manifestations of the disease included spastic dyskinesia (in early disease stages) and cerebellar atrophy. Through systematic rehabilitation, the daily life of patients with this movement disorder was improved. This case report adds to the literature on spinocerebellar ataxia type 8 by summarizing its features.